Ulvan extraction from two types of green algae Ulva and studying the effect of pH and temperature on the yield - ديب, جورج; البودي, حسن; تقلا, محمود (Latakia University Journal -Biological Sciences Series, 2022)
In this study, ulvan (sulphated polysaccharide) was extracted from two species of green algae: Ulva fasciata and U.lactuca, which were collected from the Syrian coast and calculate the yield for each, in addition to study the effect of pH and temperature on the yield. The results showed that U. fasciata was superior to U. lactuca in ulvan content where the yield was 27.35% and 24.38% respectively at reference condition of, upon modifying in the extraction conditions, the yield of two types increased until it reached 29.55% and 27.11% respectively, at a temperature of 850 C and pH=2, while the lowest yield was 9.75% of Ulva lactuca at pH=1 and 950 C opposite 10.43% of U. fasciata at pH=1 and 750 C.